The Formulation and Physical Stability Test Of Gel Fruit Strawberry Extract (Fragaria x ananassa Duch.) - Rahmawati, Desi Ana; setiawan, Iwan (Universitas Muhammadiyah Surakarta, 2019)
Strawberry fruit (Fragaria x ananassa Duch,) is one of the traditional plants that has various bioactive compounds including phenol compounds, vitamin C, flavanoids and ellagic acid. Strawberry fruit functions as an antioxidant and antibacterial so strawberry extract can be used as gangrene wounds in diabetes mellitus The purpose of this study was to determine the effect of the gel gelling agent formula variation on its physical properties so that it can be know which formula best meets the gel physical standard.The type of research used was experimental research. The research, includes extracting strawberry fruit using maceration method. Gel with strawberries in 4 formulas, with each formula having a different base concentration of carbobol 940. Formula 1 with a concentration of 0.5%, formula 2 concentration of 1.0%, formula 3 concentration of 1.5% and formula 4 concentration of 2.0%. The gel that has been made is then tested for physical stability which includes organoleptic test, pH test, homogeneity test, adhesion test, dispersion test, viscosity test, protection power test and gel acceptability.The results of the study showed that in the organoleptic test, pH test, dispersion test, viscosity test, adhesion test, and protection test as well as acceptability the formula had the best spread and stickness and the overall standard.